You need to use the following substitution `1 - u^2 = t` , such that:

`1 - u^2 = t=> -2udu = dt=>u du = -(dt)/2`

`int u*sqrt(1 - u^2) du = -(1/2)*int sqrt t dt`

`-(1/2)*int sqrt t dt = (-1/2)*(t^(3/2))/(3/2) + c`

Replacing back `1 - u^2` for t yields:

`int u*sqrt(1 - u^2) du = (-1/3)*((1 - u^2)^(3/2)) + c`

**Hence, evaluating the indefinite integral, yields` int u*sqrt(1 - u^2) du = -((1 - u^2)^(3/2))/3 + c` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now